Setting up Confessional Borders: The Uniates and the Orthodox in Hunedoara County in a Time of “Temptation” (1759-1761) - MIRON, Greta-Monica (Studia Universitatis Babeș-Bolyai Historia, 2017)
In this study, I aim to reconstruct the distribution of religious denominations in the county of Hunedoara and to present the dynamics of conversion from the Uniate to the Orthodox faith and vice versa in the first half of the 18th century, with particular emphasis on the Orthodox movement led by the monk Sofronie from Cioara (1759-1761). The case study reveals the balance of power between the episcopacy and the local clergy, the centralizing tendencies of the former and the centrifugal tendencies of the latter (as evinced by the ordinations that took place outside the diocese and by several priests’ attempts to operate in the parish without the consent of the bishop). The presence of Orthodox priests, alongside Uniate clerics, in the parishes of this county throughout the first half of the century showed that they had become accustomed to one another, so much so that, following the movements of conversion to the Orthodox faith, just their proportions changed, in favour of Orthodoxy. The time of the Sofronian conflict was a time of harsher delineations between the Orthodox and the Uniates, primarily as an effect of Sofronie’s anti-Union discourse, which took over some of the themes of the Orthodox propaganda from the past, more precisely, from the time of Visarion, and resumed the allegations that had been made against the Uniate priests, reactivating or strengthening thus some older fears instilled in the faithful. Moreover, the Uniate bishop was facing now a new crisis of Union with the Church of Rome after that triggered by Visarion. This time he found himself in a more delicate position: on the one hand, he established lines of demarcation between the Uniates and the Orthodox through the confessions of allegiance to the Union that he elaborated; on the other hand, he needed to fluidize the denominational borders and to encourage a comeback to the Union in order to recover the lost territory. The apostate priests’ return to the Uniate Church was a negotiated phenomenon, which had to take into account the local context and the local resistances. Rezumat: Crearea de frontiere confesionale: uniți și ortodocși într-un timp al „ispitei” în comitatul Hunedoarei (1759-1761). Mi-am propus să reconstitui tabloul confesional din comitatul Hunedoara, dinamica alunecărilor dinspre unire înspre ortodoxie și invers din prima jumătate a secolului al XVIII-lea, cu insistență asupra mișcării ortodoxe a călugărului Sofronie din Cioara (1759-1761). Studiul de caz dezvăluie raportul de putere dintre episcopie și clerul local, tendințele centralizatoare ale celei dintâi și tendințele centrifuge ale clerului (sesizabile îndeosebi prin hirotonirile în afara diecezei, prin funcționarea în parohie fără acordul episcopal). Prezența în parohii a preoților ortodocși alături de cei uniți pe tot parcursul primei jumătăți a secolului arată că s-au obișnuit unii cu ceilalți, astfel că în urma mișcărilor ortodoxe s-au schimbat doar proporțiile, în favoarea ortodoxiei. Confruntat cu noua configurație ecleziastică, episcopul unit s-a aflat într-o poziție delicată: pe de o parte, prin mărturisirile de unire elaborate a stabilit linii de demarcație între uniți și neuniți, pe de altă parte, avea nevoie să fluidizeze frontierele confesionale, să încurajeze revenirile la unire pentru a recupera teritoriul pierdut. Reintrarea în rândul Bisericii unite a fost o acțiune negociată în funcție de contextul local, de rezistențele locale. Cuvinte-cheie: Transilvania, comitatul Hunedoarei, Biserica unită, Biserica ortodoxă, conflict confesional, frontieră confesională, apostazile, convertire.